2010
DOI: 10.1038/ng.536
|View full text |Cite
|
Sign up to set email alerts
|

Common variants at 7p21 are associated with frontotemporal lobar degeneration with TDP-43 inclusions

Abstract: Frontotemporal lobar degeneration (FTLD) is the second most common cause of presenile dementia. The predominant neuropathology is FTLD with TAR DNA binding protein (TDP-43) inclusions (FTLD-TDP)1. FTLD-TDP is frequently familial resulting from progranulin (GRN) mutations. We assembled an international collaboration to identify susceptibility loci for FTLD-TDP, using genome-wide association (GWA). We found that FTLD-TDP associates with multiple SNPs mapping to a single linkage disequilibrium (LD) block on 7p21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
536
2
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 512 publications
(573 citation statements)
references
References 30 publications
31
536
2
4
Order By: Relevance
“…4 Follow-up studies confirmed the importance of TMEM106B in FTLD and suggested that TMEM106B may influence risk for FTLD-TDP by modulating the levels of the secreted growth factor progranulin (GRN). 5 Here, we study the role of TMEM106B in the pathologic presentation of AD using TMEM106B SNP rs1990622, previously associated with reduced levels of GRN in human plasma.…”
mentioning
confidence: 87%
“…4 Follow-up studies confirmed the importance of TMEM106B in FTLD and suggested that TMEM106B may influence risk for FTLD-TDP by modulating the levels of the secreted growth factor progranulin (GRN). 5 Here, we study the role of TMEM106B in the pathologic presentation of AD using TMEM106B SNP rs1990622, previously associated with reduced levels of GRN in human plasma.…”
mentioning
confidence: 87%
“…located 6.9 kbp downstream of the gene transmembrane protein 106B (TMEM106B), has been shown to potentially modify both age at onset for GRN-mutation carriers and GRN levels in healthy individuals and GRN-mutation carriers. [30][31][32] Furthermore, inconclusive results on APOE as a modifying factor for FTLD have been reported. 17,18,[33][34][35][36] It has also been speculated that rs5848 in the 3 0 UTR of GRN is a binding site for the micro-RNA miR-659 and may regulate the translation of the GRN mRNA.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…5,6 Genome-wide association studies in sporadic and familial ALS demonstrated highly significant association with single-nucleotide polymorphisms (SNPs) across a 170-Kb region at 9p21.2. [7][8][9][10][11] A massive GGGGCC hexanucleotide repeat expansion mutation (HREM) has recently been identified within intron 1 of C9ORF72 as the pathogenic mutation responsible for familial and sporadic ALS and FTD in these cases. 12,13 Here we describe HREM mutation frequencies in ALS in five European populations.…”
Section: Introductionmentioning
confidence: 99%